An analysis of the openness of historical archives:based on the 'Rekidai Hōan' - Zhao, Wenwen (Journal of Modern Social Sciences, 2025)
The significance of archives in historical research cannot be overstated. As primary sources, they offer invaluable insights into the past, shaping our collective memory and understanding of the world. Over time, many historical archives have been gradually opened and declassified, granting researchers access to historical truths that were previously inaccessible during the events themselves. However, while archives appear to be increasingly open and transparent, their accessibility remains a complex issue.With advancements in digital technology, archival materials can now be accessed remotely, seemingly providing unrestricted availability. Yet is the archive truly and fully open? Despite expanded access, archives do not necessarily offer a complete reconstruction of history, even for scholars. The historical record remains fragmented, and researchers must continually piece together evidence in pursuit of a more comprehensive understanding of the past.This article examines the openness of archives through an analysis of Rekidai Hōan (『歷代寶案』), focusing on the fundamental nature of archives, the impact of digital archiving, and a comparative study with oral historical sources.
Keywords: Openness of Archives; Digital Archiving; Rekidai Hōan; Memory Construction